Online information acquisition affects food risk prevention behaviours: the roles of topic concern, information credibility and risk perception - Zhenwu You; Weizhen Zhan; Fan Zhang (BMC, 2023)
Abstract Background The COVID-19 pandemic has not only brought great challenges to the global health system but also bred numerous rumours about food safety. Food safety issues have once again attracted public attention. Methods The data were drawn from the fifth wave of the first Taiwan Communication Survey database. The respondents were selected via multistage stratified random sampling. The sampling units were townships/districts, villages/neighbourhoods and households. The sample consisted of 2098 respondents. This study first used propensity value matching to analyse the direct impact of online food safety information acquisition on preventive behaviours and examined the heterogeneous impact caused by the difference in the degree of topic attention through value matching. Hayes' PROCESS macro model 6 was applied to confirm the mediating effect and the serial mediating effect. Results The research results show that an increase in the frequency of the acquisition of online food safety information significantly increases individuals' food risk prevention behaviour. However, only users with high concern about the issue are affected. The food risk prevention behaviour of users with low concern about this issue is not affected by the acquisition of online food safety information. Further analysis shows that risk perception and information credibility both play mediating roles in the impact of online food safety information acquisition on food risk prevention behaviour. Moreover, the transmission and united effects of information credibility and risk perception play a distal mediating role. Conclusions Food risk prevention behaviours are an important topic for personal health as well as government management. Our study's findings can provide empirical evidence for risk managers and decision-makers to reevaluate the role of the internet in food risk management.